A study on identifying the phenotypic saturation thresholds of broomcorn millet based on functional limits and growth models - Xiao Cui; Huiqin Li; Jiangchen Zan; Jianhua Cui; Pengzhi Hou; Linjuan Wang; Wenfeng Guo; Zhifang Bi; Fuzhong Li; Yuanhuai Han; Xiaoying Zhang; Yushen Wang (PLoS ONE, 2025)
Broomcorn millet, renowned for its strong stress tolerance and rich nutritional value, serves as a crucial germplasm resource in the arid and semi-arid regions of northern China. It exhibits advantages such as a short growth period, high water use efficiency, salt tolerance, and pest resistance, which guarantee the stability of grain supply in local areas. Accurately identifying its growth saturation threshold is one of the core elements of precision agriculture technology and has become a research hotspot in the field of agricultural science both domestically and internationally in recent years.In this study, 8 representative broomcorn millet varieties were selected from typical dryland farming areas in Shanxi Province. Based on functional limits and growth models, temporal identification and comparative analysis of the phenotypic saturation thresholds of these 8 varieties were conducted, providing a scientific basis for variety selection and precision cultivation in arid regions.The Logistic model was used to fit the plant height growth dynamics, yielding a growth limit of 134.86–171.74 cm and a threshold achievement time of 59.60–73.80 days, with a model fitting degree R 2 > 97%. The Richards model was applied to fit the stem diameter growth, resulting in a growth limit of 8.47–10.28 cm and a threshold achievement time of 70.50–182.20 days, with an R 2 also > 97%. A quadratic polynomial regression model was employed to simulate the dynamic changes in chlorophyll content (R 2 > 70%), clarifying the chlorophyll content characteristics of different plant parts.The results indicated significant differences in plant height, stem diameter, and chlorophyll content thresholds among different varieties. Pinshu 4 ranked first due to its dual advantages in plant height and stem diameter; Xiaohongruan Proso Millet 6 followed closely by virtue of its high photosynthetic efficiency; White Proso Millet 8 showed balanced performance in stem diameter and chlorophyll content; Jinshu 7 had stable plant height and relatively high chlorophyll content; the remaining varieties ranked lower due to weak performance in one or more traits.